Effects of concanavalin A on the progesterone production by bovine steroidogenic luteal cells in vitro - Destro, F. C.; Martin, I.; Landim-Alvarenga, Fdc; Ferreira, Jcp; Pate, J. L. (Wiley, 2016)
The aim of this study was to evaluate the effects of concanavalin A (CONA) on the progesterone (P4) production by bovine steroidogenic luteal cells (LCs) in vitro. Luteal cells were collected during the mid-luteal stage (at 10-12 days following ovulation) and processed in the laboratory. Luteal cells were grown for 7 days in a humid atmosphere with 5% CO2 , with or without 10% foetal bovine serum, and were subjected to the following treatments: control: no treatment; CONA (10 μg/ml); LH (100 μg/ml); CONA + LH; LH (100 μg/ml) + prostaglandin F2α (PGF2α) (10 ng/ml); CONA + LH + PGF2α. Samples of the culture media were collected on days 1 (D1) and 7 (D7) for P4 quantification. The cells were counted on D7 of culture. Differences between treatments were considered statistically significant at p < .05. Culture in the presence of CONA decreased the P4-secreting capacity of LCs on D7 of culture, particularly in the absence of serum. The cell numbers did not change between treatments.